Processo de enfermagem nas escolas de nível técnico e superior de Mato Grosso : estudo sobre concepções e práticas educativas docentes - Bottosso, Rosa Maria (2014)
ABSTRACT: This research aimed at understanding the nursing process from the concepts and educational practice of the professor/nurse and/or coordinator of the nursing courses in nursing schools at technical and university levels in Mato Grosso, Brazil. The philosophy of the Gramscian practice was reference for this study. The technical schools reaserched were located in the site of the National Professional and Technological Education Information System and the higher level courses in the e-MEC site. Twenty-eight subjects were selected based on the criteria of being a nurse, acting in the teaching area and having experience in care giving. The thematic analysis guided the treatment of the materials that were collected through interviews, questionnaires and observation, resulting in three themes: 1- Memories of learning: (i) Wanda Horta in the nurses’ memories; (ii) Difficulties to learn the nursing process: criticism of the school and the professors; (iii) Marginalization of the writing of the nursing care: medical record denied; (iv) Priority in the preparation of biologicist technicians. 2- Conceptions and experiences. (i) SAE, MAE or process? (ii) Nursing process as an instrument of work; (iii) Omission and pain: care in the assistance practice. 3- Teaching practice: proximities and distances: (i) Nursing process in technical courses; (ii) Nursing process in university courses; (iii) Nursing process in the integration between services and teaching; (iv) Shared considerations. The data revealed that the nursing process, despite showing to the subjects the main instrument of nursing work, is not totally understood nor developed in technical and university courses. Most of the professors’ knowledge is fragmented, suggesting a distance between theory and practice in the educational and social context. The underlying ideology that separates those that are graduated to perform (technical work – nursing technician - homo faber) and those graduated to think about care (intellectual work - nurse - homo sapiens) came about, reproducing the old conflicts resulting from the social division of work. The study showed that the weaknesses in the concepts and educational practices of the nursing teacher lie in the domain of the educational work and in the organization of the course. One of the challenges to change the ―know how/do‖ in a hegemonic practice in schools points to the need to change the orientation of teaching in the sense of historical and political reflections on health and nursing practices. By doing this, the nursing process can become consolidated as an important instrument of collective work, able to aggregate strength to the practice of nursing care in the social context.